2020
DOI: 10.1177/2325967119893920
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroscopic Surgery in Middle-Aged Patients With Meniscal Symptoms: A 5-Year Follow-up of a Prospective, Randomized Study

Abstract: Background: Arthroscopic meniscal surgery is a common orthopaedic procedure in middle-aged patients, but the efficacy of this procedure has been questioned. In this study, we followed up the only randomized controlled trial that has shown a 1-year benefit from knee arthroscopic surgery with an exercise program compared with an exercise program alone. Purpose: To (1) evaluate whether knee arthroscopic surgery combined with an exercise program provided an additional 5-year benefit compared with an exercise progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…In other words, patients having undergone APM had higher risk for OA development and progression (Sihvonen et al 2020 ). A similar finding was reported by Sonesson et al ( 2020 ) among patients randomized to APM or nonoperative treatment. Registry data from England showed that patients who had undergone an APM had a 2–3 times higher risk of total knee replacement compared with the general population (Abram et al 2019a ).…”
Section: Up-to-date Evidence For Apmsupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, patients having undergone APM had higher risk for OA development and progression (Sihvonen et al 2020 ). A similar finding was reported by Sonesson et al ( 2020 ) among patients randomized to APM or nonoperative treatment. Registry data from England showed that patients who had undergone an APM had a 2–3 times higher risk of total knee replacement compared with the general population (Abram et al 2019a ).…”
Section: Up-to-date Evidence For Apmsupporting
confidence: 89%
“…In their RCT, Gauffin et al ( 2014 ) reported that arthroscopic surgery provided better pain relief compared with nonoperative treatment at 1 year follow-up in people with meniscal symptoms. In a follow-up study, the trialists found that positive effects of surgery had diminished at 3- and 5-years’ follow-up and radiologic deterioration had become more common in the surgery group (Gauffin et al 2017 , Sonesson et al 2020 ).…”
Section: Up-to-date Evidence For Apmmentioning
confidence: 99%
“…However, the 3-year as-treated data also found that participants with meniscal symptoms had less improvement in KOOS pain score with APM. The 5-year follow-up data from this study again demonstrated a statistically significant greater reduction in KOOS pain score for those without meniscal symptoms in the APM group (20). As noted by Gauffin et al, meniscal symptoms may be nonspecific and not necessarily reflect meniscal pathology (18).…”
Section: Discussionsupporting
confidence: 70%
“…Another recently published 5 year follow-up of a randomised trial reported radiographic deterioration in 60% of patients in the surgery group and 37% in the non-surgery group (p=0.060). 32 However, all this evidence is subject to considerable uncertainties, as the observational data are prone to confounding by indication while the trial data 30 32 are hampered by high rates of crossover (around 25–30%) from non-operative treatment to surgery during the follow-up and high loss to follow-up (around 30%).…”
Section: Discussionmentioning
confidence: 99%